Manga, Wuxia and (New) Religious Syncretisms: The Orientalization of the Western Imaginary, from Osamu Tezuka to Contemporary Oriental Disciplines - Porrovecchio, Alessandro (Journal of religion, media and digital culture, 2013)
A new interest in various forms of spirituality and religiosity is emerging in some subcultures of contemporary society. This tendency can be seen as an indicator of an Orientalization process that affects everyday life and lifestyles, and it can be read as a symptom of a crisis in the paradigm of Western Modernity, which is changing the relationship between culture and nature, the central role played by the rational positivist paradigm, and ideas of body, space and time. Oriental disciplines and martial arts are a significant case study for the purpose of analyzing the ongoing Orientalization process. These highly ritualized practices have become part of many people’s daily life and have affected their way of dressing, as well as the way they arrange furniture at home and the way they make decisions that involve their diet and body care. These practices may also affect people’s identities by changing their values, ethics and morality. To explore the Orientalization process, I first introduce some features of the diffusion of the “mythical Orients” in the Western imaginary since the sixties. In particular, I focus on some media products (for example, mangas and wuxia movies) that played an important role in arousing interest in Other cultures. In this stage I will refer to some media theories, in particular to Gerbner's cultivation theory and to the medial socialization effect. In a second step I focus on the imaginary embodied in some Oriental disciplines and martial arts. I refer to some results of a research that I am conducting in some martial arts gyms, starting from my experience as an instructor. In that context I performed an ethnographic study, gathering several in-depth interviews with masters, beginners, fighters, experts and therapists, and analysing the interactions within some online communities (virtual ethnography). This last method allowed me to come back to the first step, and to focus on how some features of the media imaginary are mediated through the interactions within the virtual communities.